Relevance of research of the pharmacological properties of salvia (Salvia officinalis) (literature review) - Ye.V. Zalyhina (Medičnì Perspektivi, 2022)
Salvia officinalis (sage) attracts attention as it is widely cultivated on the territory of Ukraine. It is known that it has long been used in traditional medicine, as it contains large amounts of borneol, camphor, caryophyllene, cineole, ale, humulene, chilling, pinene and thujone. The purpose of this review is to collect and analyze information on the relevance of using the medicinal properties of raw Salvia officinalis (sage), since it reveals oncoprotective, antimutagenic, antioxidant, hepatoprotective, anti-inflammatory, antimicrobial, antifungal action, normalizes metabolic processes, and has successfully proven itself in the composition of cosmeceuticals. Taking into account the current COVID-19 pandemic situation in the world, as well as the anti-inflammatory, antimicrobial, antiviral properties of Salvia officinalis (sage), its positive effect on the normalization of the level of lipid peroxidation, antioxidant enzymes (superoxide dismutase and catalase), as well as a significant effect on reducing pulmonary fibrosis, dosage forms based on Salvia officinalis, can be used for prevention, comprehensive treatment and rehabilitation after a COVID-19 infection. The analysis of the pharmaceutical market showed that in Ukraine, medicines based on Salvia officinalis are used in the treatment of diseases of the upper respiratory tract, as well as in climacteric syndrome and psychoemotional stress, in the complex therapy of chronic diseases of the gastrointestinal tract and genitourinary system. The collected and systematized information indicates that medicinal plant Salvia officinalis (sage) can be used in a more diverse way. Therefore, we consider it expedient to further study the pharmacological properties of Salvia officinalis and develop a technology for the manufacture of new dosage forms for internal use based on it.